Best-Practice Project: STEAM and Cooperative Learning to Improve Understanding of Global Warming - Ambarwulan, Diah (MJI Publisher, 2025)
STEAM and Cooperative learning have become effective approaches in enhancing students' understanding of scientific concepts, including global warming.This study aims to evaluate the effectiveness of applying STEAM and Cooperative methods in enhancing the understanding of global warming among 10th-grade IKM 11 students at MAN 1 Kota Bekasi.The methods used include creating infographics based on Canva, simple experiments modeling the greenhouse effect, and assessments based on Google Form.The research results show that the average student assessment scores increased from 64.03 (previous material) to 85.89 (after the implementation of the method).Additionally, the analysis of data distribution shows a more uniform improvement in understanding among students.Factors supporting the success of this method include project-based learning, technology integration, and active interaction in group discussions.Thus, the implementation of the STEAM and Cooperative learning models not only improves student learning outcomes but also contributes to the Sustainable Development Goals (SDGs) Goal 4 (Quality Education) and Goal 13 (Climate Action), as well as supporting Indonesia's Golden Vision 2045 in building superior and competitive human resources.